The Influence of Organizational Culture on Employee Satisfaction and Loyalty at PT. Sarana Naju Lestari Banggai - Mandang, Novaria; Arfan Syahputra, Muh; Milang, Alwiyah; Layoo, Nurhidayah (Yayasan Pendidikan Belajar Berdikari, 2025)
This study aims to analyze the influence of organizational culture, work motivation, and job satisfaction on employee loyalty in an organization. The results showed that organizational culture has a positive and significant influence on job satisfaction (O = 0.200; T-Statistics = 1.377; P-Value = 0.004) and employee loyalty (O = 0.351; T-Statistics = 3.141; P-Value = 0.002). In addition, work motivation is also proven to have a positive and significant effect on job satisfaction (O = 0.754; T-Statistics = 5.218; P-Value = 0.000) and employee loyalty (O = 0.355; T-Statistics = 2.682; P-Value = 0.008). Job satisfaction has a positive influence on employee loyalty (O = 0.284; T-Statistics = 3.675; P-Value = 0.000). However, job satisfaction does not significantly moderate the relationship of work motivation to employee loyalty (O = -0.084; T-Statistics = 0.778; P-Value = 0.437) nor the relationship of organizational culture to employee loyalty (O = 0.147; T-Statistics = 1.337; P-Value = 0.182).These findings provide important managerial implications for organizations in increasing employee satisfaction and loyalty through strengthening organizational culture and strategies to increase work motivation. Thus, companies can increase employee engagement and retention in the long run.